A Direct Measurement of the Activation Potential of Stainless Steels in Nitric Acid. Issue 9 (23rd June 2017) - Laurent, B.; Gruet, N.; Gwinner, B.; Miserque, F.; Tabarant, M.; Ogle, K.
Abstract : The rate of anodic dissolution and the associated activation potential that characterizes the passive-active transition of stainless steels have been measured directly for the first time in nitric acid. The anodic dissolution current under cathodic polarization in pure nitric acid, in absence of chlorides, is masked by intense cathodic hydrogen reduction. In this work, atomic emission spectroelectrochemistry (AESEC) was used to record simultaneously the dissolution rate of the individual alloying elements of stainless steels as well as the overall cathodic current. This methodology has been used to quantify the influence of several parameters on the activation potential: nitric acid concentration, temperature, and the addition of silicon in the steel composition.